Ionospheric effects of sudden stratospheric warming during moderate-to-high solar activity: Case study of January 2013 - Goncharenko, L. (2013)
A major sudden stratospheric warming (SSW) occurred in January 2013 during moderate-to-high solar activity conditions. Observations during the winter of 2012/2013 reveal strong ionospheric disturbances associated with this event. Anomalous variations in vertical ion drift measured at the geomagnetic equator at Jicamarca (12°S, 77°W) are observed for over 40 days. We report strong perturbations in the total electron content (TEC) that maximize in the crests of equatorial ionization anomaly, reach 100% of the background value, exhibit significant longitudinal and hemispheric asymmetry, and last for over 40 days. The magnitude of ionospheric anomalies in both vertical drifts and TEC is comparable to the anomalies observed during the record-strong SSW of January 2009 that coincided with the extreme solar minimum. This observation contrasts with results of numerical simulations that predict weaker ionospheric response to the tidal forcing during high solar activity.